Story and situation : narrative seduction and the power of fiction - Chambers, Ross; Godzich, Wlad. (Minneapolis : University of Minnesota Press, 1984)
Studies the relation between teller and listener in a set of French, English, and American short stories from the nineteenth and early twentieth centuries.
Chapter Nine: Authority and Seduction: The Power of FictionAppendix A: Saki, "The Open Window"; Appendix B: Marcel Schwob, "Les Sans-Gueule"; Bibliography; Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 24, 2019).
JSTOR
Keywords: Fiction -- Technique; Narration (Rhetoric); Fiction -- History and criticism; Narration; Roman -- Technique; Roman -- Histoire et critique; LITERARY COLLECTIONS -- General; Fiction; Fiction -- Technique; Narration (Rhetoric); Criticism, interpretation, etc